Foreign Aid in the Aftermath of Large Natural Disasters - Ilan Noy; Oscar Becerra; Eduardo A. Cavallo (Inter-American Development Bank (IDB), 2012)
This paper examines Official Development Assistance (ODA) in the aftermath of large natural disasters between 1970 and 2008. Using an event-study approach, the paper finds that while the median increase in ODA is 18 percent compared to pre-disaster flows, the typical surge is small in relation to the size of the affected economies. Moreover, aid surges typically cover only 3 percent of the total estimated economic damages caused by the disasters. The main determinants of post-disaster aid surges are found to be the intensity of the event itself and the recipient countrys characteristics such as level of development, country size and stock of foreign reserves. The paper does not find evidence that political considerations or strategic behavior on the part of donors determine the size of post-disaster aid surges.
Keywords: F35; Q54; 330